Analysis of the possibility of applying a residual magnetic field for lack of fusion detection in welded joints of S235JR steel - Złocki Arkadiusz; Roskosz Maciej; Krakowski Tomasz; Mucha Tomasz (Open Engineering, 2025)
The purpose of the conducted research was to verify the possibility of detecting one of the most dangerous defects in welded joints, which are lack of fusion, on the basis of measurements and analysis of residual magnetic field distributions. The radiographic method was used as a reference method, giving a real picture of welding imperfections occurring in the samples. Two types of sensors, a fluxgate sensor and a magnetoimpedance sensor, were used in magnetic field measurements. A calibration procedure was developed and applied for each of them. Residual magnetic field distributions were obtained from the measurement results. Based on these, the distributions of gradients and relative gradients were determined. Comparison of the obtained results with radiographs showed the possibility of detecting a lack of fusion on the basis of magnetic images of welded joints. In addition, the possibility of using both types of magnetic field sensors for magnetic imaging of lack of fusion in welded joints was demonstrated.